Perception survey of crisis and emergency risk communication in an acute hospital in the management of COVID-19 pandemic in Singapore - Lai Meng Ow Yong; Xiaohui Xin; Jennifer Mei Ling Wee; Ruban Poopalalingam; Kenneth Yung Chiang Kwek; Julian Thumboo (BMC, 2020)
Abstract Background Emergency risk communication is a critical component in emergency planning and response. It has been recognised as significant for planning for and responding to public health emergencies. While there is a growing body of guidelines and frameworks on emergency risk communication, it remains a relatively new field. There has also been limited attention on how emergency risk communication is being performed in public health organisations, such as acute hospitals, and what the associated challenges are. This article seeks to examine the perception of crisis and emergency risk communication in an acute hospital in response to COVID-19 pandemic in Singapore and to identify its associated enablers and barriers. Methods A 13-item Crisis and Emergency Risk Communication (CERC) Survey, based on the US Centers for Disease and Control (CDC) CERC framework, was developed and administered to hospital staff during February 24-28, 2020. The survey also included an open-ended question to solicit feedback on areas of CERC in need of improvement. Chi-square test was used for analysis of survey data. Thematic analysis was performed on qualitative feedback. Results Of the 1154 participants who responded to the survey, most (94.1%) reported that regular hospital updates on COVID-19 were understandable and actionable. Many (92.5%) stated that accurate, concise and timely information helped to keep them safe. A majority (92.3%) of them were clear about the hospital's response to the COVID-19 situation, and 79.4% of the respondents reported that the hospital had been able to understand their challenges and address their concerns. Sociodemographic characteristics, such as occupation, age, marital status, work experience, gender, and staff's primary work location influenced the responses to hospital CERC. Local leaders within the hospital would need support to better communicate and translate hospital updates in response to COVID-19 to actionable plans for their staff. Better communication in executing resource utilization plans, expressing more empathy and care for their staff, and enhancing communication channels, such as through the use of secure text messaging rather than emails would be important. Conclusion CERC is relevant and important in the hospital setting to managing COVID-19 and should be considered concurrently with hospital emergency response domains.